Personality factors as predictors of foreign language aptitude - Biedroń, Adriana (Studies in Second Language Learning and Teaching, 2011)
The study addresses a problem which is inadequately investigated in second language acquisition research, that is, personality predictors of foreign language aptitude. Specifically, it focuses on the Five Factor model which includes Openness to Experience, Conscientiousness, Extraversion, Agreeableness and Neuroticism (Costa & McCrae, 1992) as traits differentiating gifted and nongifted foreign language learners and predicting results of foreign language aptitude tests. Although contemporary researchers generally agree that affect is an important variable in second language acquisition, most empirical studies demonstrate that personality factors are weakly correlated with cognitive abilities and that their contribution to the ultimate attainment is minor (cf. Robinson & Ellis, 2008). On the other hand, these factors constitute an integral part of cognitive ability development (cf. Dörnyei, 2009); therefore, neglecting them in research on foreign language aptitude would be unjustified. The following study is an attempt to analyze the Five Factors in two groups of learners: gifted and nongifted. In order to answer the question as to which and to what extent personality factors have a predictive effect on foreign language aptitude, the results were subjected to a multiple regression analysis. The findings of the study are presented and discussed in a wider context of research on cognitive abilities.